Social determinants of health related to stay-at-home order adherence and social distancing attitudes among a diverse Deep South population - Jennifer L. Lemacks; Tammy Greer; Sermin Aras; Laurie Abbott; Darlene Willis; June Gipson; Mohamed O. Elasri (BMC, 2021)
Abstract Objective To describe COVID-19 related symptoms and medical care experienced in the first six months of the pandemic as well as stay-at-home order adherence, and attitudes related to COVID-19 risk and social distancing among a diverse sample of adults in the Deep South. Methods Survey data were collected from 411 Louisiana and Mississippi residents for three weeks in June 2020 through social media. Results Over half (52.5%) of participants who experienced COVID-19 related symptoms (with 41.5% experiencing at least one symptom) did not feel the severity of symptoms warranted seeking medical care. 91.6% of the Deep South adults visited certain places or did activities where visiting or gathering with other people was involved during stay-at-home mandates. Religiosity/spirituality, age, education, number of children in the home, attitudes related to COVID-19 risk of complications and social distancing were related to the greater/lesser likelihood of stay-at-home order adherence. Conclusions Various cultural and contextual factors were related to stay-at-home order adherence. Understanding how social values, life stage, socioeconomic, and geographic factors influence stay-at-home order adherence would lead to more effective policy design to improve population adherence.